2017
DOI: 10.1159/000468145
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Iron Replacement Improves Quality of Life in Hypoferritinemic Inflammatory Bowel Disease Patients with and without Anemia

Abstract: Background: No study has compared changes in quality of life (QoL) following iron therapy between anemic and non-anemic, hypoferritinemic patients. This study compares the impact of parenteral iron replacement on QoL in inflammatory bowel disease (IBD) patients with anemia, or in those with hypoferritinemia alone. Methods: Consecutive IBD patients diagnosed with anemia or hypoferritinemia were enrolled. IBD questionnaire (IBDQ) and 36-Item Short Form Survey (SF36) at diagnosis and 6 weeks post treatment were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…Thus, a placebo-controlled, double-blinded, randomized study in women with iron deficiency but without anaemia indicated that intravenous iron administration resulted in an improvement of fatigue in 82% of patients in the intervention group compared with 47% in the placebo group and that the effect of iron supplementation on fatigue was most pronounced in women with an initial ferritin concentration of less than 15 ng/mL [ 174 ]. Similar beneficial effects of intravenous iron administration regarding quality of life in non-anaemic patients with IBD have recently been published [ 175 , 176 ]. Thus, none of these observational, single centre studies included a placebo control given the high incidence of placebo mediated benefits on quality of life in such patient cohorts [ 174 , 177 ].…”
Section: Evidence Of Managementmentioning
confidence: 58%
“…Thus, a placebo-controlled, double-blinded, randomized study in women with iron deficiency but without anaemia indicated that intravenous iron administration resulted in an improvement of fatigue in 82% of patients in the intervention group compared with 47% in the placebo group and that the effect of iron supplementation on fatigue was most pronounced in women with an initial ferritin concentration of less than 15 ng/mL [ 174 ]. Similar beneficial effects of intravenous iron administration regarding quality of life in non-anaemic patients with IBD have recently been published [ 175 , 176 ]. Thus, none of these observational, single centre studies included a placebo control given the high incidence of placebo mediated benefits on quality of life in such patient cohorts [ 174 , 177 ].…”
Section: Evidence Of Managementmentioning
confidence: 58%
“…The Short Form (SF)‐36 physical component summary significantly increased in 13 IBD patients with non‐anaemic iron deficiency receiving iron therapy . In the same way, the SF36 mental component score is improved with iron supplementation in both anaemic and non‐anaemic iron‐deficient IBD patients. In the FERGICOR trial, treatment with both IV iron compounds (ferric carboxymaltose and iron sucrose) were associated with significant improvement in Inflammatory Bowel Disease Questionnaire IBDQ scores from baseline to week 12 ( P < 0.001) .…”
Section: Resultsmentioning
confidence: 73%
“…In a study enrolling 85 non‐anaemic iron‐deficient IBD patients, IV iron sucrose supplementation significantly improved quality of life assessed with the Inflammatory Bowel Disease Questionnaire (IBDQ) and the SF‐36 Health Survey . Another small study evaluated quality of life with IBDQ and SF‐36 in 10 patients with anaemia and 13 with hypoferritinemia treated with IV iron polymaltose . Improvements in quality of life in hypoferritinemic patients were similar to those with anaemia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of anemia should not be overlooked and should be started as soon as possible, as iron replacement improves quality of life of anemic and hypoferritinemic patients with IBD [ 21 ]. The decision to initiate the therapy and route of administration depend on a number of factors including the general condition of the patient, IBD activity, anemia severity and the prior tolerance of oral iron preparations.…”
Section: Management Of Iron Deficiency Anemiamentioning
confidence: 99%